Gastón Pérez Alfaro y Facundo Cruz (coord.) (2021). Después del terremoto. El sistema político argentino a 20 años de la crisis del 2001. 388 págs. Ciudad Autónoma de Buenos Aires: China Editora. ISBN: 978-987-47449-4-4.: The Argentine political system after 20 years of 2001 crisis. - Tamer, Guido (América Latina Hoy, 2022)
The review pretends to browse narrowly but in detail through many things included in Después del terremoto, coordinated by Gastón Pérez Alfaro and Facundo Cruz, about the effects produced by the crisis in Argentina in 2001 in areas like the political system, the Judicial Power, political identities, foreign affairs, etc., after 20 years.